Program Studi Ilmu-ilmu Sosial dan Kemanusiaan di Institut Teknologi Bandung - Ciri dan Kebutuhan Relevan - Prof. Wiranto Arismunandar (Jurnal Sosioteknologi, 2006)
The following is the summary of paper presented by Professor Wiranto Arismunandar concerning the establishment of a study program spesialising in the social sciences and humanities in Institut Teknologi Bandung. The idea is stimulated by the fact that the appreciation of the society on the advances of technologies and sciences as well as their products and services has not been so satisfactory. He, therefore, suggests that ITB establish a study program in which the students specialize themselves in social sciences and humanities. The students are expected to be able to interact equally with the scientists and engineers and able to inform the society the developments and advances of technologies and sciences when they graduate. In order to produce competent graduates to carry out the above-mentioned expertises, he recommends that basic sciences and mathematics, communication skills, and other relevant social sciences and humanities be taught to this group of students.